The war on rescue : the obstruction of humanitarian assistance in the European migration crisis - Plowright, William, 1982- (Cornell University Press, 2024)
"Humanitarian assistance aids those suffering most, from war, disaster, and disease. However, sometimes governments block aid organizations from helping. This book uses examples around the world to theorize how and why governments do this. It then uses this framework to analyze obstruction of aid during the European Migration Crisis (2015-2022)"-- Provided by publisher.
Keywords: Humanitarian assistance.; Humanitarian assistance -- Europe -- History -- 21st century.; Europe -- Emigration and immigration -- Government policy -- History -- 21st century.; Aide humanitaire.; Aide humanitaire -- Europe -- Histoire -- 21e siècle.; Europe -- Émigration et immigration -- Politique gouvernementale -- Histoire -- 21e siècle.; SOCIAL SCIENCE / Regional Studies; Electronic books.